Pandangan Ibnu Qudamah Tentang Nafkah Istri Qobla Dukhul - Abdul Halim (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2024)
The Fuqoha' stipulate that there are three reasons that make a person obliged to provide support to other people, namely because of marriage, kinship and ownership. A legal marriage gives rise to consequences in the form of the husband's obligation to provide a living for his wife, whether the wife is rich or poor, because what underlies the existence of a living is the marriage contract or the marriage itself. However, when does a husband begin to pay a living, it is mandatory for a husband to give his wife, Qabla Dukhul or Ba'da Dukhul. The focus of the study is the view of Ibn Qudamah, who has a different view from most of the Hanabilah ulama' regarding providing maintenance for wives of Qobla Dukhul and what legal Istinbat he uses regarding providing maintenance for wives of Qobla Dukhul. The method used is Library Research, while the data used is e-documentary literature so as to get a clear picture of Ibn Qudamah's views regarding the livelihood of Qobla Dukhul's wife. The conclusion is that in Ibn Qudamah's view, a husband does not have to give qobla dukhul income because the wife has not completely surrendered it to her husband to have sex with him and have fun with him, namely Tamkin tam. The legal istinbat is based on qiyas, namely making qiyas with a young wife and is based on the Hadith of the Prophet narrated by Imam Bukhari regarding the marriage of the Prophet Saw with Sayyidah Aisyah Ummil Mu'minin, where at that time Sayyidah Aisyah was still 6 years old.